Spontaneous tumor lysis syndrome (STLS) during biopsy for burkitt lymphoma: a case report - Sirui Pan; Qiyang Shen; Jianfeng Zhou; Tao Li (BMC, 2024)
Abstract Background Tumor lysis syndrome (TLS) is a hematologic oncological emergency characterized by metabolic and electrolyte imbalances. On breakdown of tumor cells, enormous amounts of potassium, phosphate, and nucleic acids are released into systemic circulation. TLS mainly occurs during chemotherapy. However, there are rare incidences of spontaneous tumor lysis syndrome (STLS) prior to commencement of therapy. Case presentation In the case being reported, the child had just undergone a biopsy. As the incision was being closed, there was a sudden onset of high fever, arrhythmia, severe hyperkalemia, hypocalcemia, and acidosis. Following timely symptomatic treatment and continuous renal replacement therapy(CRRT), the child's laboratory results improved, and organ function was restored to normal. The final pathological diagnosis confirmed Burkitt lymphoma. The boy is currently on maintenance chemotherapy. Conclusions TLS is a potentially life-threatening complication in hematologic oncology. Several important conclusions can be drawn from this case, reminding clinicians to: (1) be fully aware of the risk factors of TLS and evaluate the level of risk; (2) pay attention to the possibility of STLS during operation, if surgical procedures are necessary and operate with minimal trauma and in the shortest time possibly; (3) take preoperative prophylaxis actively for high-risk TLS patients, including aggressive fluid management and rational use of diuretics and uric-acid-lowering drugs. In addition, this case confirms the effectiveness of CRRT for severe STLS.